Analisis Struktur Gerak Tari Zapin Siak Di Kecamatan Siak Kabupaten Siak Provinsi Riau - Tiya Melinda; Afifah Asriati (FBS Universitas Negeri Padang, 2020)
Zapin Siak dance is a traditional Malay dance which has been cultured, lived, and developed in line with human life from time to time. Zapin Siak dance is danced by two male dancers taking parallel position in a form of motion which generally uses a lot of. This is a qualitative research using a content analysis method, known as content analysis. The object of research was Zapin Siak Dance in Kampung Dalam Subdistrict, Siak District, Siak Regency, Riau Province. The data used were primary and secondary data. The data were collected through literature study, observation, interview, and documentation. The research instrument used was the researcher itself and was assisted by writing instruments, cameras, and flash drives. The data analysis was done by describing and interpreting various movements of the Zapin Siak dance. It refers to the elements of motion: the head, body, hands, and The results show that the movement structure of Zapin Siak Dance in Siak District, Siak Regency, Riau Province, consists of 22 kinem elements, 22 morphokinem elements, 7 motif elements, and one overall dance form, namely Zapin Siak dance. Zapin Siak dance has a syntagmatic relationsip between the motif level and a paradigmatic relationship in overall dance.